Effects of temporary erosion control blanket and grass cover on the rates of runoff and sediment in the cut and fill slopes of forest roads using a rainfall simulation test - Behnaz Askari; Mehran Nasiri; Majid Lotfalian (پژوهشنامه مدیریت حوزه آبخیز, 2024)
Extended Abstract Background: Soil erosion is one of the global problems that threatens water and soil resources. Protecting and recovering bare and uncovered soils, as well as diverting surface runoff from the soil, are an efficient method for reducing soil erosion in sensitive and erosion-prone areas. Among the activities to prevent soil erosion are to maintain the natural vegetation of the area and stabilize bare and uncovered soils with the help of temporary or permanent methods. The use of erosion control blankets is a soil bio-engineering method that can effectively reduce runoff and sediment and increase slope stability. Therefore, the current research aimed to temporarily stabilize soil using protective covering treatments, such as jute, straw, wood chips, Festuca grass cover, and nano zeolite super absorbent, to reduce the amount of runoff and sediment. Methods: The study area is the Darabkola Forest (the educational-research forest of Sari University of Agricultural Sciences and Natural Resources), with an area of  about 2612 hectares located in the southeast of Sari City between 52° 14′ E and 36° 28′ N. To measure the amount of runoff and sediment in the Darabkola Forest, plots with dimensions of 70 x 50 cm and a depth of 10 cm were created using galvanized sheets. Then, plots were placed on the ground with a slope of 3%. Erosion control blanket treatments made of jute filled with wood chips, straw, and nanozeolite superabsorbents were prepared and located in the plots, as well as jute cover, jute cover with Festuca grass, and Festuca grass. Rain simulation tests were conducted for each sample (30 minutes with an intensity of 50 mm.h-1) and the amount of runoff from the plots was measured at 5-minute intervals using a graduated cylinder placed at the bottom of the plots. Sediment concentration was measured by weighing the samples after settling the runoff and passing it through filter paper. Sediment concentration was calculated by dividing the amount of sediment by the volume of runoff. Data were analyzed using one-way ANOVA for seven treatments. Duncan's test was used to compare the means. Pearson's correlation analysis was also used to investigate the relationship between runoff and sediment concentration in runoff. Results: The results of statistical analysis showed that the highest amount of runoff (0.77 mm.h-1) belonged to the control treatment, and the lowest amount was recorded in the treatment of straw and the Festuca herbaceous species (0.24 and 0.27 mm.h-1, respectively). Overall, the straw treatment reduced the amount of runoff by 69% and the Festuca herbaceous species treatment reduced it by 64% compared to the control plot. The results of sediment concentration revealed 63% and 52% decreases in the amount of sediment in the samples belonging to the treatment of jute cover and jute cover together with Festuca species, respectively, compared to the control plot. The highest sediment concentration was measured in the control sample (7.13 g/ml). The presence of Festuca in the soil reduced the sediment by 2%, which shows that the presence of a herbaceous species such as Festuca does not considerably reduce the sediment concentration compared to the other treatments such as jute. Examining the coefficients obtained from Pearson's correlation analysis between runoff rate and sediment concentration in runoff for different treatments indicated that the stabilizer addition to the soil reduced sediment and reduced surface runoff in some treatments. A positive and significant correlation was found between runoff and sediment in wood chips, straw, Fesuka, and nanozeolite treatments, while a negative and significant correlation was recorded for Jute + Festuca and the Jute treatment. Conclusion: This research demonstrates that the use of erosion control blankets with combinations of different materials, such as straw and stubble, nanozeolite, and wood chips, along with the Festuca grass cover, can reduce runoff volume and reduce soil erosion and waste, especially in forest road trenches containing soils without vegetation. Moreover, grass cover (such as Festuca) increases water permeability in the soil and prevents soil loss. Therefore, using these erosion blankets can reduce soil erosion around forest roads.